PSYCHOLOGICAL AND PEDAGOGICAL FACTORS FOR THE DEVELOPMENT OF THE FUTURE SPECIALISTʼS SUBJECTIVE POSITION - Vovk, Valentina (PSYCHOLOGICAL JOURNAL, 2017)
The principle of orientation to the subject approach to learning became priority in the context of the social and economic transformations that take place today in our society. The purpose of which is a creation of the most favorable conditions for self-development and formation of the student’s personality, identification and active use of its individual characteristics and organization of pedagogical interaction, in which the future specialist would be included subjectively. In our opinion, the subjective position of the future specialist is an integrative multicomponent psychological phenomenon that are determined by the system of meaningful, valuable and semantic attitudes to the learning, to the chosen profession, to himself as a specialist and to the own future professional way that are aimed at self-development and self-actualization. Based on the theoretical and empirical researches we identified and substantiated the psychological and pedagogical factors, that are contributes to the development of a student’s subjective position during a period of study at a higher school. Among them: Actuality of the subjective interaction through the educational dialogue. Assistance in acquiring subjective experience in the process of educational and professional activity of students. Increasing self-regulation and self-control. Harmonization of self-assessment and self-esteem. Development of reflexive abilities.